(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Currently, accidents are a major problem for everyone. The risks are increasing day by day, so efforts are being made to avoid reducing their effects. We live in a world where traffic laws are unimportant and are frequently violated. Moreover, its human nature to withstand what is imposed upon them. As a consequence, using a different perspective, provides security with elegant and smart features using smart helmet. Two of the modules are in the helmet and each bike works in sync, to ensure wearing a motorcyclist helmet. Radio waves are responsible for the cable connection between the helmet and the bike chain. The Piezo power generator is used to determine speed and this function is optimized to limit the speed of the user. The ALCHO-LOCK function is used to stop alcohol and driving: Accelerometer detects accidents, and this is communicated through the use of the GSM module in our area, which is designed specifically to send a message for personal contact and the relevant authority of the person concerned. In traffic accidents and fog infections due to fog or smog is also. Another applicationknown as E-HELMET allows to reduce the amount of money needed by virtual reality users without stopping their rider from stopping and paying for it.